Metallophyte and heavy metal tolerance of common fern species - Abu Bakar, Ainaa Eliah; Othman, Rashidi; Mohd Hatta, Farah Ayuni (Nova Science Publishers, Inc., 2024)
The toxic heavy metal pollution of soil and water is a major and global environmental concern as heavy metals can easily enter bio-geochemical cycles. As such, significant efforts should be made to mitigate or, at the very least, decrease their spread and destruction. Although increased human activity can lead to sustainable development, it impacts the surrounding environment and, potentially, disrupts the stability of river ecosystems. For instance, the rapid development of agriculture and urbanisation significantly increases the risk of polluting aquatic plants and systems with heavy metals, with toxic contaminants already being detected in some polluted water systems. After angiosperms, ferns are the second largest type of vascular plants. For more than 360 million years, they have played an important role in shaping the biodiversity of plant life on Earth. However, the lack of a high-quality genomic sequence of ferns has hindered our understanding of the biological functions of their genes and their potential applications in agriculture, the environment, and health. As ferns are known to accumulate heavy metals, they are an excellent indicator of any ecosystem deterioration and a potential phytoremediation plant for heavy metal-polluted systems. Plants have developed mechanisms; such as chelation and sequestration via various ligands; that regulate the uptake and accumulation of both essential and non-essential heavy metals. Therefore, ferns may be used as metallophyte or hyperaccumulator of heavy metal-polluted ecosystems.